2018
DOI: 10.1177/1460408618767703
|View full text |Cite
|
Sign up to set email alerts
|

The management of penetrating neck injury

Abstract: Penetrating neck injuries are serious as there is a high concentration of vital structures in close proximity to each other in a compressed anatomical area. Penetrating neck injuries can be immediately life threatening due to massive bleeding from vascular structures or due to airway compromise. Injury to the digestive tract in the neck may also result in delayed and potentially life-threatening conditions. The majority (79%) of penetrating neck injuries can be managed conservatively. The clinician caring for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
1
56

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(82 citation statements)
references
References 41 publications
3
22
1
56
Order By: Relevance
“…[ 12 ] While relatively uncommon in comparison to other mechanisms of injury, the potential morbidity of penetrating neck trauma is apparent, given the high density of vital structures confined to a relatively small and poorly protected area. [ 13 14 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] While relatively uncommon in comparison to other mechanisms of injury, the potential morbidity of penetrating neck trauma is apparent, given the high density of vital structures confined to a relatively small and poorly protected area. [ 13 14 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…This algorithm states that those with hard signs of injury should proceed directly to exploration, whilst those with soft signs of injury should undergo CT‐A, and only if positive, continue to the operating theatre. Some studies add that high impact mechanisms, such as gunshots, in asymptomatic patients should still undergo CT‐A 29 . Our review identified three studies 14,19,21 examining the ‘no zone’ approach, all of which demonstrated its safety with no complications or missed injuries in those conservatively managed.…”
Section: Discussionmentioning
confidence: 99%
“…However, damage to the pharyngeal, oesophageal, spinal cord and nerves are also very common. [ 2 ] Although this patient was incredibly fortunate that there was no life-threatening bleeding or tracheal rupture, he presented with phrenic nerve palsy, which resulted in DP.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high concentration of vital structures in a small anatomic area, penetrating neck injuries are associated with substantial morbidity and mortality. [ 2 ] As a result, the Advanced Trauma Life Support guidelines recommend that vessels and airway injuries should be identified first during the early stages of the evaluation. However, damage to the pharyngeal, oesophageal, spinal cord and nerves are also very common.…”
Section: Discussionmentioning
confidence: 99%